2012
DOI: 10.1080/15228916.2012.727744
|View full text |Cite
|
Sign up to set email alerts
|

Government Quality Determinants of Stock Market Performance in African Countries

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
132
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 208 publications
(163 citation statements)
references
References 56 publications
25
132
0
6
Order By: Relevance
“…Ultimately, low inflation in Africa would improve opportunities for efficient alternative forms of investment in compensation for the failed privatization projects. Consistent with Asongu (2012Asongu ( , 2013a SSA's share of Foreign Direct Investment (FDI) averages 1% of global flows (Bartels et al, 2009) and there is a pressing need for generation of private capital flows that are complementary to FDI (Rolfe & Woodward, 2004). Low inflation will ease the recommendation of Darley (2012) in the expansion of regional trade arrangements as key to looking outside traditional flows of FDI to Africa, which have been largely limited by political economy considerations, regulatory uncertainty, skills, labor, regulation and exchange rate volatility (Bartels et al, 2009;Tuomi, 2011).…”
Section: Inflation Monetary Policy and African Businesssupporting
confidence: 64%
See 1 more Smart Citation
“…Ultimately, low inflation in Africa would improve opportunities for efficient alternative forms of investment in compensation for the failed privatization projects. Consistent with Asongu (2012Asongu ( , 2013a SSA's share of Foreign Direct Investment (FDI) averages 1% of global flows (Bartels et al, 2009) and there is a pressing need for generation of private capital flows that are complementary to FDI (Rolfe & Woodward, 2004). Low inflation will ease the recommendation of Darley (2012) in the expansion of regional trade arrangements as key to looking outside traditional flows of FDI to Africa, which have been largely limited by political economy considerations, regulatory uncertainty, skills, labor, regulation and exchange rate volatility (Bartels et al, 2009;Tuomi, 2011).…”
Section: Inflation Monetary Policy and African Businesssupporting
confidence: 64%
“…Firstly, with the dramatic rise in the price of stable food commodities over the past decade 2 , while the literature on the causes and impacts of the crisis in global food prices in the developing world has mushroomed in recent years (Piesse & Thirtle, 2009;Wodon & Zaman, 2010;Masters & Shively, 2008), we are unaware of studies that have closely examined how financial policies affected consumer prices. Hence, correcting inflation is particularly important in fighting poverty (Funjii, 2011) on the one hand and; on the other hand directly (Ibeh et al, 2007;Acquaah et al, 2008;Musila & Al-Zyoud, 2012) or indirectly (Asongu 2012(Asongu , 2013aBartels et al, 2009;Rolfe & Woodward, 2004;Tuomi, 2011) eases the doing of business in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…The insignificant effect of Polity IV has a twofold explanation: the time and level hypotheses for the benefits of democracy. In line with Asongu (2012b), the time and level hypotheses have been documented: in many countries in Africa (Lemarchand, 1972), Southeast Asia (Scott, 1972), India (Wade, 1985) and Turkey (Sayari, 1977); post 1990 communist countries like Russia (Varsee, 1997) and: many Latin American countries upon different waves of democratization (Weyland, 1998). …”
Section: Updated Financial Dynamics and Modified Pri Measurementmentioning
confidence: 80%
“…On the one hand, economic prosperity could be associated with higher levels of private investment. On the other hand, recent African institutional literature has shown that wealtheffects matter in institutional quality (Asongu, 2012c;2013b) …”
Section: Determination Of Fundamental Characteristicsmentioning
confidence: 99%